COT-30 Effect of tumor resection in 11C methionine accumulation area on survival in patients with glioblastoma. (6th December 2021) - Ohmura, Kazufumi; Ohwashi, Etsuko; Ikegame, Yuka; Takei, Hiroaki; Miwa, Kazuhiro; Yano, Hirohito; Yokoyama, Kazutoshi; Kumagai, Morio; Shinoda, Jun; Daimon, Takashi; Nakayama, Noriyuki; Iwama, Toru
Abstract: Aim: The amount of tumor excised in an area enhanced by contrast medium on magnetic resonance imaging strongly affects the survival time of patients with glioblastoma. We investigated the effect of the amount of tumor removal in the 11C methionine (MET) accumulation site on overall survival(OS). Methods: Twenty-six patients (15 male; mean age, 68.9 years) with a diagnosis of glioblastoma who underwent tumor resection at Kizawa Memorial Hospital between June 1, 2015 and August 30, 2021 underwent MET-positron emission tomography (MET-PET) before and after the operation. In a comparison of MET-PET before and after tumor resection, the tumor-to-normal (T/N) ratio reduction (ΔT/N), MET accumulation area reduction (MET-extent of resection [EOR]), and the residual MET accumulation volume (MET-residual tumor volume [RTV]) were calculated. The relationship between these MET-related parameters associated with tumor resection and OS was investigated via univariable analysis. Results: Univariate analysis revealed that ΔT/N was significantly associated with OS (hazard ratio [HR]: 0.98; 95% confidence interval [CI]: 0.97–0.99; p=0.02). MET-RTV was also significantly associated with OS (HR: 1.01; 95% CI: 0.98–1.02; p=0.73) Conversely, MET-EOR (HR: 0.99; 95% CI: 0.97–1.01; p=0.06) was not significantly associated with OS. Conclusions: Aggressive surgical resection of the MET accumulation site significantly prolongs survival in patients with glioblastoma.